2001
DOI: 10.1177/009102600103000201
|View full text |Cite
|
Sign up to set email alerts
|

Human Resources Management Perspective at the Turn of the Century

Abstract: The future of human resources management and the role of HR managers are presented in this paper. The paper presents the results of nine large reports that have been undertaken around the world. The market, demographic, social, and management changes taking place are addressed.Taking into account these trends, a precise role of HR managers in the future is outlined.A t the turn of the century, human resources managers will have to face new challenges. World economy and markets are different from those of a dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 8 publications
0
15
0
2
Order By: Relevance
“…Production based on information and knowledge is replacing a machine-based mode of production. Stable and protected working relations, with the underlying assumption of a lifetime career, are giving way to flexibility of work and employment [54,55]. …”
Section: Discussionmentioning
confidence: 99%
“…Production based on information and knowledge is replacing a machine-based mode of production. Stable and protected working relations, with the underlying assumption of a lifetime career, are giving way to flexibility of work and employment [54,55]. …”
Section: Discussionmentioning
confidence: 99%
“…A gestão de recursos humanos tem sido alterada e transformada em gestão estratégica de pessoas, assumindo um papel maior de importância para as empresas promovendo mudanças orga-nizacionais e respostas aos inúmeros desafios do ambiente empresarial (LIPIEC, 2001). Albuquerque (2002) destaca que os novos paradigmas para uma estratégia competitiva devem ser fundamentados no comprometimento dos colaboradores, em detrimento à importância da tecnologia, considerando as pessoas e suas ideias fundamentais para a geração de inovações geradas pelo conhecimento, estímulo à aprendizagem e à criatividade.…”
Section: Inovação Na Indústria Automobilísticaunclassified
“…The empirical research of Beaver et al (2003) and Burchell (2002), for example, found that HR managers must endeavour to create and maintain an organisation that should be able to deliver the plan and strategy of the business by ensuring that the HR strategy is continually aligned with the business strategy. Lipiec (2001) and Kane (2001) again believe that HRM managers need to focus more on the strategic management role of HR. Jayne (2002) furthermore suggests that there must be a tight fit between HR and business strategies in order to cope with identified trends, which invariably influence an organisations mission and strategies.…”
Section: Analysis Of the Hard Approach To The Hr Professionmentioning
confidence: 99%